Enhanced AODV Protocol for Detection and Prevention of Blackhole Attack in Mobile Ad Hoc Network - Hijazi, Sherin; Moshref, Mahmoud; Al-Sharaeh, Saleh (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2017)
Mobile Ad-hoc Network (MANET) is a kind of wireless network that has the most challenging network infrastructure. It is formed using the mobile nodes without any centralized administration from the security perspective and is a self-configuring fastest emerging wireless technology, each node on the MANET will act like a router which forwards the packets. Dynamic nature of this network makes routing protocols to play a prominent role in setting up efficient route among a pair of nodes. Dynamic Source Routing (DSR) and Ad-hoc On-Demand Distance Vector (ADOV) is a reactive MANET routing protocols. Most of the attacks on MANETs are routing protocol attacks. Attacks on routing protocols, especially internal attacks will cause the damage to MANETs. Sinkhole and black hole attacks are a type of internal attack which is affected by attempting to draw all network traffic to malicious nodes that fake routing update and degrade the performance of the network. The black hole nodes should be detected from the network as early as possible via detection mechanism and should also guarantee the higher detection rate and less cross-over error rate. In this paper, we studied the characteristics of black hole attack and how it will affect the performance of the distance vector routing on demand routing protocol such as (ADOV) protocol, which recognizes the presence of black hole node from packet flow information between nodes and isolates it from the network via applying AODV protocol that one of popular routing protocol. We have evaluated the performance of the system using widely used simulator NS2, results prove the effectiveness of our prevention and detection method.